Impact of dehydration on a full body resistance exercise protocol - Kraft, J. A.; Green, J. M.; Bishop, P. A.; Richardson, M. T.; Neggers, J. H.; Leeper, J. D. (European Journal of Applied Physiology, 2010)
This study examined effects of dehydration on a full body resistance exercise workout. Ten males completed two trials: heat exposed (with 100% fluid replacement) (HE) and dehydration (~3% body mass loss with no fluid replacement) (DEHY) achieved via hot water bath (~39°C). Following HE and DEHY, participants performed three sets to failure (using predetermined 12 repetition maximum) of bench press, lat pull down, overhead press, barbell curl, triceps press, and leg press with a 2-min recovery between each set and 2 min between exercises. A paired t test showed total repetitions (all sets combined) were significantly lower for DEHY: (144.1 ± 26.6 repetitions) versus HE: (169.4 ± 29.1 repetitions). ANOVAs showed significantly lower repetitions (~1-2 repetitions on average) per exercise for DEHY versus HE (all exercises). Pre-set rate of perceived exertion (RPE) and pre-set heart rate (HR) were significantly higher [~0.6-1.1 units on average in triceps press, leg press, and approached significance in lat pull down (P = 0.14) and ~6-13 b min-1 on average in bench press, lat pull down, triceps press, and approached significance for overhead press (P = 0.10)] in DEHY versus HE. Session RPE difference approached significance (DEHY: 8.6 ± 1.9, HE: 7.4 ± 2.3) (P = 0.12). Recovery HR was significantly higher for DEHY (116 ± 15 b min-1) versus HE (105 ± 13 b min-1). Dehydration (~3%) impaired resistance exercise performance, decreased repetitions, increased perceived exertion, and hindered HR recovery. Results highlight the importance of adequate hydration during full body resistance exercise sessions.